2015 IEEE Power and Energy Conference at Illinois (PECI) 2015
DOI: 10.1109/peci.2015.7064881
|View full text |Cite
|
Sign up to set email alerts
|

Power system state estimation based on Iterative Extended Kalman Filtering and bad data detection using normalized residual test

Abstract: This paper proposed an enhanced real-time state estimation using Iterative Extended Kalman Filtering (IEKF). The IEKF estimated state variables based on past state variables. Largest Normalized Residual Test (LNRT) was integrated with IEKF for bad data detection. A comparison with the conventional Weighted Least Squares (WLS) was also investigated using the IEEE 14 bus test system simulated in MATLAB. Based on the results, the merits and limitations of IEKF were summarized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The results show that ACKF has a consistently better computation performance compared with the WLS and IEKF methods. It is also found that IEKF has a heavier computation compared with WLS, which is consistent with the previous research [36].…”
Section: Computation Efficiencysupporting
confidence: 92%
“…The results show that ACKF has a consistently better computation performance compared with the WLS and IEKF methods. It is also found that IEKF has a heavier computation compared with WLS, which is consistent with the previous research [36].…”
Section: Computation Efficiencysupporting
confidence: 92%
“…The IEKF algorithm to enhance its bad data detection capability of the IEKF algorithm is enhanced when LRNT was applied. IEKF was unable to accurately identify the location of bad data eventhough the detection scheme was able to determine faulty measurements [20].…”
Section: Alternative Formulation Of Bddimentioning
confidence: 99%
“…The integration of renewable energy further reduces lifecycle emissions, resulting in a net environmental benefit. Climate Change Mitigation: Carbon Footprint Reduction: The adoption of renewable energy and electric vehicles plays a crucial role in mitigating climate change by reducing emissions of greenhouse gases, particularly carbon dioxide (CO2) [87]. By transitioning to renewable electricity for EV charging, businesses can significantly reduce their carbon footprint and contribute to global efforts to limit global warming and its associated impacts.…”
Section: Environmental and Economic Impactsmentioning
confidence: 99%